Acute Toxicity and Behaviour of Fresh Water Murrel (Channa punctata, Bloch 1793), Exposed to Agricultural Pesticides - Chakraborty, Debjit; Mondal, Debashri (International Journal of Ecology and Environmental Sciences, 2025)
Pesticides are employed in agricultural practices to manage insect infestations. However, they can significantly impact all levels of biological organization, particularly affecting fish, populations and contaminating surface waters through mechanisms such as irrigation or precipitation-driven runoff. This investigation examined the acute toxicity of several commonly used pesticides in croplands, including Chlorpyrifos (20%), Cypermethrin (10%), and Hamla550 (combination of Chlorpyrifos 50% and Cypermethrin 5%), utilizing static renewal bioassay experiments. Fingerlings of both edible and ornamental fish, specifically Channa punctata, with an average size of 8.16±0.86 cm and a body weight of 7.53±0.65 g, were selected for the study. The 96 hr LC50 (Probit) values Chlorpyrifos, Cypermethrin, and Hamla550, were determined to be 1.3836, 0.2841, and 0.0010 mg L-1, respectively. The physicochemical parameters of the test water were analyzed following standard protocols. The behavioural responses of the exposed fish were monitored throughout the exposure period. As the concentrations of the toxic pesticides increased, the fish exhibited various abnormal behaviours, including hyperactivity, erratic swimming, patterns, heightened surface activity, rapid and erratic movements, body imbalance, and loss of equilibrium. This study highlights the importance of assessing appropriate pesticide dosages prior to field application to help preserve fish populations.